Integrated weed management in vegetable crops - Dubey, R. P. (Indian Farming, 2018)
Frequent irrigations and application of farmyard manure andfertilizers induces heavy infestation of weeds in vegetable crops and reduce the crop yields drastically. The critical period of crop-weed competition varies from 15 to 30 days in okra and between 30 and 70 days in onion. Cultural methods such as manual weeding, stale seed-bed technique, mulching, soil solarization in vegetable nurseries, drip irrigation etc. help in reducing weed problem.Integration of pre-emergence herbicides with intercultural operations (hoeing, earthing-up, mulching) has been found effective and economical.